Decentralised‐distributed hybrid voltage regulation of power distribution networks based on power inverters. Issue 3 (15th January 2019) - Wang, Yu; Xu, Yan; Tang, Yi; Syed, Mazheruddin Hussain; Guillo‐Sansano, Efren; Burt, Graeme M.
Abstract : In modern power distribution networks, voltage fluctuations and violations are becoming two major voltage quality issues due to high‐level penetration of stochastic renewable energies (e.g. wind and solar power). In this study, a hybrid control strategy based on power inverters for voltage regulation in distribution networks is proposed. Firstly, a decentralised voltage control is designed to regulate voltage ramp‐rate for mitigating voltage fluctuations. As a beneficial by‐product, the var capacity from the inverters become smoothed. Then, a distributed voltage control is developed to fairly utilise the var capacity of each inverter to regulate the network voltage deviations. Furthermore, once there is a shortage of var capacity from inverters, on‐load tap changers control will supplement to provide additional voltage regulation support. The simulation results on IEEE 33‐bus distribution network with real‐world data have validated the effectiveness of the proposed voltage regulation method.